Perceptions of Male and Female Teachers About Organizational Culture of Paragon City Schools System Lahore - Sumaira Munawar; Khadija Sittar; Misbah Malik (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2019)
The study was aimed to investigate the perceptions of male and female teachers about organizational culture of Paragon City School System Lahore. Teachers who were taught students of grade 4-12 were the population of this study. Sample was comprised of 171 teachers selected through census sampling technique. 43 teachers were male and 128 teachers were female in the sample. A Likert type instrument was developed in which 13 statements were related to tacit assumption, 10 statements with values and 9 statements were relevant to the norms. Reliability of the instrument items was 0.818 which showed that the questionnaire was accurate. Findings of the study indicated that male and female teachers have differences of opinions regarding human nature, human relationships, openness, intimacy, teamwork, support colleagues, and students' help, is being valued in DHA school system in Lahore. Whereas no significant difference regarding truth and reality, trust, cooperation, criticism on principal, and handling discipline, between male and female teachers. It is recommended that principal would create a school culture where discipline handling, criticism on principal, cooperation and trust between teachers may develop.